Capital structure puzzle: Does shariah compliance status matter? - Halim, A.A.; Sukor, M.E.A.; Bacha, O.I. (2017)
The capital structure puzzle remains largely unanswered. Although some light have been shed on the dynamic forces that shapes the typical firm’s debt-to-equity mix, the case of the Shariah firm’s capital structure behaviour remains even more of a mystery. This paper attempts to investigate the capital structure behaviour of Shariah compliant firms of various levels as well those firms who are consistently Shariah noncompliant in Malaysia. The paper utilises a unique dataset of firms of heterogeneous level of Shariah compliancy status over a 20-year period from the year 1997 to 2016. The paper focuses on the effects of dynamic forces behind capital structure variation such as the optimal capital structure behavior based on the trade-off, pecking order, market timing and firm fixed effect models of capital structure. This study documents significant evidences in support of the trade-off theory with a high speed of adjustment (SOA) as well as for the time invariant firm fixed effects across all Shariah compliancy group. Nevertheless, this study’s findings show that there are evidences to suggest a moderate trend whereby as the Shariah compliancy group descend, stronger and stronger evidences of market timing behaviour appear amongst other things. This study suggests that segregating firms into different Shariah compliancy groups reveals a rich and diverse area of study which has never been delved in.